The impact of organisational culture as a context of interpersonal meaning on the management of organisational diversity - Charmain Dombai; Sonja Verwey (Communicare)
Changes in the South African business environment is placing South African business organisations under increasing pressure to move toward democratic, non-racial and fully representative organisational structures. In an attempt to accelerate this process, companies are embarking on affirmative action and black empowerment programmes in order to develop previously disadvantaged groups and to assimilate these groups into existing organisation cultures. The results of these efforts are viewed with interest and scepticism. This article explores the link between organisational communication and successful diversity management. An overview of existing literature indicates that successful diversity management is facilitated by communication processes through which sufficient shared or negotiated meaning and agreed upon language and behaviours appropriate to the workplace are constructed. This article explores the importance of interpersonal communication in organisational sensemaking through the framework of the Schemata Model of Interpersonal Communication in Organisational Contexts. The results of the empirical research indicate that individuals’ experiences of the organisational culture as a context for the construction of meaning, are more important to diversity management than individual value differences as a result of diversity in terms of age, gender or race.